Kemandirian dan Pemberdayaan Ekonomi Santri dalam Menghadapi Tantangan Ekonomi Global (Studi Kasus pada Pondok Pesantren Al-Mawaddah Jekulo Kudus) (Institut Agama Islam Negeri Kudus, 2023)
This study aims to determine the implementation of self-sufficiency and economic empowerment of students in facing global economic challenges and the supporting and inhibiting factors at the Al-Mawaddah Jekulo Kudus Islamic Boarding School. This research uses a type of field research (field research). Data collection techniques used are: observation, interviews, and documentation. After the data was collected, it was analyzed using interactive model qualitative analysis techniques, through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of this study obtained the implementation of students' economic independence in facing global economic challenges at the Al-Mawaddah Jekulo Kudus Islamic boarding school, namely by: (1) Carrying out entrepreneurship for students by utilizing the facilities provided by the pesantren. (2) Holding training and seminars for students and the surrounding community. The implementation of the economic empowerment of students in facing global economic challenges at the Al-Mawaddah Jekulo Kudus Islamic boarding school is by: (1) Providing motivation to students, aiming to foster a spirit of enthusiasm from within the students. (2) Providing knowledge about entrepreneurship, providing knowledge about entrepreneurship. While the supporting factors in carrying out independence and empowerment at the Al-Mawaddah Jekulo Kudus Islamic boarding school are: (1) There is a caregiver who is a role model for the students. (2) Advice given by caregivers to students. (3) The spirit that is embedded in the students. While the inhibiting factors in carrying out independence and empowerment at the Al-Mawaddah Jekulo Kudus Islamic boarding school are: (1) The spirit of the students is less stable. (2) Lack of supervision on goods sold at Islamic boarding schools. Penelitian ini bertujuan untuk mengetahui implementasi kemandirian dan pemberdayaan ekonomi santri dalam menghadapi tantangan ekonomi global serta faktor pendukung dan penghambatnya di pondok pesantren Al-Mawaddah Jekulo Kudus. Penelitian ini menggunakan jenis penelitian field research (penelitian lapangan). Teknik pengumpulan data yang digunakan yaitu: observasi, wawancara, dan dokumentasi. Setelah data terkumpul dilakukan analisis dengan menggunakan teknik analisis kualitatif model interaktif, melalui tahapan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini diperoleh implementasi kemandirian ekonomi santri dalam menghadapi tantangan ekonomi global di pondok pesantren Al-Mawaddah Jekulo Kudus yaitu dengan cara: (1) Melaksanakan kewirausahaan bagi santri dengan memanfaatkan fasilitas yang telah disediakan pesantren. (2) Mengadakan pelatihan dan seminar yang diperuntukkan santri maupun masyarakat sekitar. Implementasi pemberdayaan ekonomi santri dalam menghadapi tantangan ekonomi global di pondok pesantren Al-Mawaddah Jekulo Kudus yaitu dengan cara: (1) Memberikan motivasi kepada santri, bertujuan untuk menumbuhkan jiwa semangat dari dalam diri santri. (2) Memberikan pengetahuan tentang kewirausahaan, memberikan pengetahuan tentang kewirausahaan. Sedangkan faktor pendukung dalam menjalankan kemandirian dan pemberdayaan di pondok pesantren Al-Mawaddah Jekulo Kudus yaitu: (1) Adanya tokoh pengasuh yang menjadi panutan untuk para santri. (2) Nasihat yang diberikan pengasuh kepada para santri. (3) Jiwa semangat yang tertanam dalam diri santri. Sedangkan faktor penghambat dalam menjalankan kemandirian dan pemberdayaan di pondok pesantren Al-Mawaddah Jekulo Kudus yaitu: (1) Semangat santri yang kurang stabil. (2) Kurangnya pengawasan pada barang-barang yang dijual pada unit usaha pesantren.